Cardiorespiratory coupling in the bottlenose dolphin (Tursiops truncatus) - Fahlman, A.; Mcknight, J. C.; Blawas, A. M.; West, N.; Torrente, A. G.; Aoki, K. (Frontiers in Physiology, 2023)
The bottlenose dolphin (Tursiops truncatus) is an intermittent breather, where the breath begins with an exhalation, followed by inhalation and an extended inter-breath interval ranging from 10-40 sec. Breathing has been shown to alter both the instantaneous heart rate (ifH) and stroke volume (iSV) in the bottlenose dolphin, with a transitory ventilatory tachycardia following the breath, and an exponential decrease to a stable ifH around 40 beats • min-1 during the inter-breath period. As the total breath duration in the dolphin is around 1 sec, it is not possible to assess the contribution of exhalation and inhalation to these changes in cardiac function. In the current study, we evaluated the ifH response by separating expiration and inspiration of a breath, which allowed us to distinguish their respective contribution to the changes in heart rate. We studied 3 individual male bottlenose dolphins trained to hold their breath between the different respiratory phases (expiration and inhalation). Our data show that inspiration causes an increase in ifH, while expiration appears to result in a decrease in ifH. These data provide improved understanding of the cardiorespiratory coupling in dolphins, and show how both exhalation and inhalation alters ifH.